Spider-Man. Homecoming [videorecording (Blu-Ray)] - Watts, Jon; Holland, Tom, 1996-; Keaton, Michael, 1951-; Favreau, Jon; Paltrow, Gwyneth, 1972-; Zendaya, 1996-; Glover, Donald, 1983-; Daly, Tyne; Tomei, Marisa; Downey, Robert, Jr., 1965- (Sony Pictures Home Entertainment, 2017)
"Peter Parker balances his life as an ordinary high school student in Queens with his superhero alter-ego Spider-Man, and finds himself on the trail of a new menace prowling the skies of New York City." --